Performance-Based Funding Dynamics for the Enhancement of Strategic Objectives of Higher Education in Sub-Saharan Africa: An Institutional Case in Cameroon - Bilola Theresia Samfoga Doh; Pascal Samfoga Doh (SCIKNOW, 2022)
Although access to higher education continues to be crucial for developing countries, higher education remains a corps of excellence with selectivity as one of its operational dynamics. Even if higher education were to be fully massified everywhere, some of its functions and objectives would remain elitist and more strategic and may often require very tough choices on the part of administrators and managers of higher education. This situation suggests the inevitability of differential concentration of funds and the enhancement mechanisms for the priorities, one of which can be represented by performance-based funding. In this article, we examine a funding scheme, the Staff Development Grant at the University of Buea, Cameroon which employed performance-funding instruments as a means of boosting the university’s teaching and research profile, a strategic priority at the time. The results suggest that performance-based funding could have important positive implications in stimulating the responsiveness of other strategic objectives of higher education in the country’s context.